An analysis of lateral stepping using proactive and reactive assessment methods in young adults - Chennimalai Ravi, Praveen Kumar; Bandi, Alekhya; Ramachandran, Sivakumar (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. Stepping is a common reactive postural control strategy. Lateral stepping is a more challenging movement and has unique biomechanical characteristics. Stepping is commonly assessed using the Balance Evaluation System Test (BESTest), waist pulls and surface translation. The speed and characteristics of stepping are critical to prevent a fall. It is important to con-sider the inﬂuence of the test construct on stepping behaviour. The aim of this study is to identify diﬀerences in stepping charac-teristics between two selected methods and determine which method elicits the most optimal stepping response as indicated by smaller spatio-temporal characteristics.Methods. Sixty healthy young adults aged between 18 and 26 years were tested for lateral stepping using the BESTest and moving platform perturbations. Video recordings of the test procedures were analysed using “TRACKER” software to measure various spatio-temporal parameters of the lateral stepping reactions, such as ﬁrst step time, balance recovery length, balance recovery time and number of steps. The Mann–Whitney U test was used to assess diﬀerences between the parameters from both methods of assessment.Results. The mean values of spatio-temporal parameters of stepping triggered by the moving platform were smaller compared to the BESTest. Furthermore, the stepping characteristics diﬀered between the two assessment methods.Conclusions. The perturbations induced by the moving platform elicited stepping responses of shorter duration and shorter distances, indicating the participants’ best stepping behaviour. The method of assessment signiﬁcantly inﬂuenced the stepping behaviour, highlighting the importance of carefully selecting an appropriate assessment for postural control testing.
Keywords: reactive postural control; lateral stepping; balance evaluation system test; surface translation